Synthesis and properties of a superphane with one thiophene and one CpCo-stabilized cyclobutadiene ring - Stäb, Silke; Gleiter, Rolf; Schaller, Rolf; Rominger, Frank (Organometallics, 2004)
A superphane consisting of one thiophene ring and one CpCo-stabilized cyclobutadiene ring, 8, was prepared in an eight-step synthesis from 5-cyclodecynol protected with tert-butyldimethylsilyl, 13. The first key step in this sequence was the reaction of 13 with zirconocene and subsequently with S2Cl2 to yield the tricyclic thiophene derivative 12. The second key step was the ring closure of 11 with CpCo(COD) to give 8. X-ray structural investigations of 11 and 8 confirmed the structural assignments. Evidence for the close proximity of the CpCo-stabilized cyclobutadiene and the thiophene rings is also given by the electronic absorption spectrum of 8 and the oxidation potential (−0.07 V).